PENGARUH KREATIVITAS, SIKAP MANDIRI, MOTIVASI DAN PENGETAHUAN KEWIRAUSAHAAN TERHADAP MINAT MAHASISWA AKUNTANSI UNTUK BERWIRAUSAHA (Studi Empiris Pada Mahasiswa Akuntansi FEB UNISMA, UMM dan UIN) - Fitriyatul Hasanah; Moh. Amin; Siti Aminah Anwar (e_Jurnal Ilmiah Riset Akuntansi, 2021)
The purpose of this research is to find out how the influence of creativity, independent attitude, motivation and entrepreneurial knowledge have a joint effect on the interest of accounting students for entrepreneurship. Empirical studies in this study is an accounting student at the Islamic University of Malang, Muhammadiyah University of Malang and Maulana Malik Ibrahim University of Malang who has taken entrepreneurship courses. The population in this study is an accounting student at the Islamic University of Malang, Muhammadiyah University of Malang and Maulana Malik Ibrahim University of Malang. Sampling technique in This research uses purposive sampling method. Sample used in the study as many as 100. Determination of the sample is done by using Slovin's formula. The results of this study indicate that creativity, independent attitude, motivation and entrepreneurial knowledge have a significant effect on interest in entrepreneurship. Keywords: Creativity, Independent Attitude, Motivation, Entrepreneurship Knowledge, Entrepreneurship Interest